Teams Games Tournament Assisted by Tic Tac Toe Media on the Effectiveness of Students in Learning - Ayatullah Muhammadin Al Fath (STAI Hubbulwathan Duri, 2021)
This study aimed to determine the effectiveness of learning in fifth-grade students at SD Negeri I Wonodadi Wetan through the Teams Games Tournament (TGT) type of cooperative learning model. The use of the Teams Games Tournament (TGT) cooperative learning model with the help of Tic Tac Toe media was chosen because the model was considered capable of growing students' enthusiasm and interest in learning effectiveness. This study uses qualitative research where this study uses analytical techniques consisting of data collection, data collection, and conclusions. Using the TGT model makes students learn from each other, causing students to work together. As for the effect of using the Teams Games Tournament (TGT) type cooperative learning model, there is an interaction between learning methods with high and low learning curiosity on the effectiveness of student learning. Cooperative Learning Method Team Game Tournament can improve learning effectiveness or performance, such as connection ability, activity, learning motivation, and student understanding.